Estudio de la distribución poblacional del caracol africano (achatina fulica b.) en cultivo de banano en la cooperativa de producción y comercialización La Clementina, cantón Babahoyo parroquia la Unión - Pinargote Ulloa, Lenin Mauricio (2017)
SUMARY In the world and more specifically in countries of center and south américa, the African Snail (Achatina fulica) has turned in the last years into a plague into different commercial plantations and of development into ornamental vegetation (parks, gardens), particularly into the plantation of Banana (Musa sp.). In the Ecuador, Achatina fulica is brought, for institutions like Agrocalidad and Department of Agriculture, Ranching, Acuacultura and Fishing (MAGAP) as a potential plague in different cultures, between these: the banana. The present work of investigation had for general aim evaluate the population distribution of African Snail (Achatina fulica) in the estate Bananera " Cooperative of Production and Commercialization La Clementina " located in the parish La Union of the canton Babahoyo; and as specific aims it was considered to determine the migratory characteristics and the physical characteristics (weight, diameter and length) of the mollusk. By means of the used methodology it was considered to be four commercial lots: "Palizada 1 ", "Palizada 2 ", "San Clemente" and "El Encanto", in which Achatina's specimens were sampled coot for 12 consecutive weeks, 3 times for week, in a time of sampling of 60 minutes, in each of the mentioned lots. The process of compilation of information in the sampling consisted of crossing afoot every lot in straight lines with sample space of 2 meters of width and (code) marked every specimen in his shell. Of every opposing individual the following information was obtained: Georreferenciación, Weight, Length, Diameter, Number of Re-captures. The opposing results indicate that the average of Achatina's tour fulica in the commercial lots they were 97,04 m, 147,77 m, 63,26 m and 94,86 m in the lots of Palizada 1, Palizada 2, San Clemente and El Encanto, respectively; being the major tour that of 147,77 m (Lot " Palizada 2 ") and having an average of 4 Individuos/m2. In what concerns the weight, the opposing average was of 13,88 gr, 17,37 gr, 29,23 gr and 19,39 gr in the lots of Palizada 1, Palizada 2, San Clemente and El Encanto, respectively; being the major weight of 29,23 gr (Lot "San Clemente"). The results of length corresponded to Palizada Uno 4,58 cm, Palizada Dos 4,72 cm, San Clemente 6,13 cm, and El Encanto 5,27 cm; whereas the results of Diameter were of: 3,20 cm, 2,63 cm, 3,36 cm and 2,84 cm for the lots of Palizada 1, Palizada 2, San Clemente and El Encanto, respectively. One concluded that Achatina fulica is distributed in each of the investigated lots, in average of 6 Individuos/m2, and with regard to the migratory characteristics, one thought that there were sampled individuals who crossed up to 33,24 meters of length, deducing that the presence of the mollusk in these distributions in the lots sampled inside the estate bananera, will increase in the next cycles of the culture and will mean that the plague will feed of the vegetable structures of the plant.